CONCEPTUAL PROVISIONS OF ESTABLISHMENT INTELLECTUAL INFORMATION CIVIL AVIATION SPACES - Lastovchenko, M. M.; Gorbunov , I. E.; Marushchak, V. I. (Problems of Informatization and Control, 2021)
The purpose and components of the intelligent information space of civil aviation are determined: intelligent systems of organization and management, an intelligent network with interfaces of control systems. The concept of the step-by-step creation of intelligent information spaces for aeroflot systems is proposed.